BRCA1/2 variants of unknown significance in hereditary breast and ovarian cancer (HBOC) syndrome: Looking for the hidden meaning. (April 2022) - Fanale, Daniele; Pivetti, Alessia; Cancelliere, Daniela; Spera, Antonio; Bono, Marco; Fiorino, Alessia; Pedone, Erika; Barraco, Nadia; Brando, Chiara; Perez, Alessandro; Guarneri, Maria Francesca; Russo, Tancredi Didier Bazan; et al.
Abstract: Hereditary breast and ovarian cancer syndrome is caused by germline mutations in BRCA1/2 genes. These genes are very large and their mutations are heterogeneous and scattered throughout the coding sequence. In addition to the above-mentioned mutations, variants of uncertain/unknown significance (VUSs) have been identified in BRCA genes, which make more difficult the clinical management of the patient and risk assessment. In the last decades, several laboratories have developed different databases that contain more than 2000 variants for the two genes and integrated strategies which include multifactorial prediction models based on direct and indirect genetic evidence, to classify the VUSs and attribute them a clinical significance associated with a deleterious, high/low or neutral risk. This review provides a comprehensive overview of literature studies concerning the VUSs, in order to assess their impact on the population and provide new insight useful for the appropriate patient management in clinical practice. Graphical Abstract: ga1 Highlights: 10–20% of patients undergoing germline BRCA1/2 genetic screening harbor VUS. Identifying potentially pathogenic BRCA1/2 VUSs may allow their re-classification. Knowing the correct VUS meaning could improve the patient clinical management.